Methane emission baseline for livestock and rice systems: Colombia - Garzon Leniz, Carlos Andres; Costa Junior, Ciniro (2025)
This Story Map presents the baseline study on methane (CH₄) emissions from livestock and rice systems in Colombia, developed within the framework of the IMEO Colombia Baseline. It integrates project activities—from data consolidation and advanced field measurements with respirometry chambers and polyethylene tunnels, to spatial analysis and improvements that aim to contribute to the national emissions inventory—in an interactive and visual format. Designed as a tool to support research, policy, and outreach, the Story Map summarizes methods, findings, and impacts, providing an accessible platform for communicating how robust methane data can inform mitigation strategies and strengthen Colombia's climate commitments.